Remote project management: challenges and best practices - Machado, Daniela Simões Martins (2022)
With the advance of technology, such as the internet and media communications, the world has become much more connected. People have shortened the physical distance through technology facilitations. This advance not only has affected the social side of humanity, but has also opened up doors so that organizations could take part of these benefits. People were trained and encouraged to work from home. Companies saw an opportunity to reduce costs and get the most qualified professionals regardless of their geographic location. In this way, Project Management (PM) with Remote Teams (RT) has taken a relevant place inside organizations. In face of the pandemic situation the world is undergoing, working remotely stopped being an option and became the way to move on. There is an uncountable study on scientific community about PM talking about issues, challenges, best practices, frameworks and other topics, but only a few of them is direct related with remote project management (RPM) and/or RT. To fill this gap, this research aims to identify the main RPM challenges as well as the practices to mitigate such challenges. To evaluate and demonstrate findings, 30 qualitative interviews were performed and 69 surveys were applied with Project Managers who are developing their activities in a remote mode 100% of the time after the beginning of the Covid-19 pandemic. In the end, it is possible to see a list of 14 challenges and 13 best practices they had to apply to maintain their projects in the track and support their teams in this such difficult moment. The author concluded that was a disruptive moment for both workers and companies. Increased quality of life and flexible schedules were identified as a great benefit. On the other hand, much more dedicated work-hours were needed to maintain projects productivity.